Degradable photo-thermal antibacterial composite film based on MXene loaded epsilon-polylysine as well as preparation and application of degradable photo-thermal antibacterial composite film
Through electrostatic self-assembly, MXene and ε-polylysine (ε-PL) were combined to prepare a photothermal antibacterial packaging film, which solves the problems of complex, time-consuming and low sterilization efficiency of the existing photothermal antibacterial packaging film preparation process, and realizes a degradable photothermal antibacterial packaging film with simple operation, low light power and high sterilization efficiency.
Patent Information
- Application Number
- CN202411846800.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing photothermal antibacterial packaging film preparation process is complex and time-consuming, with high light power, single sterilization types, long sterilization time, and simple operation, low light power and high sterilization efficiency. There is a lack of solutions for degradable photothermal antibacterial packaging films.
MXene and ε-polylysine (ε-PL) were combined by electrostatic self-assembly method to prepare MX@PL composite nanomaterials, which were added to chitosan film liquid, and a photothermal antibacterial and degradable packaging film was prepared by solvent casting.
It realizes a degradable photothermal antibacterial packaging film with simple operation, low light power and high sterilization efficiency. It can show more than 99% photothermal antibacterial properties against common food-borne pathogens such as Staphylococcus aureus and E. coli, and has good photothermal stability and repeatability.
Smart Images

Figure CN119798731A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of antibacterial and degradable packaging films, and specifically relates to a degradable photothermal antibacterial composite film based on MXene-loaded ε-polylysine, and a preparation method and application thereof. Background Art
[0002] Ensuring food safety for a growing global population is one of the most important challenges of the 21st century. In particular, infection by foodborne pathogens can not only cause a series of foodborne diseases, but also lead to food spoilage and corruption. Food packaging can not only protect food ingredients from spoilage, but also prevent them from being damaged by the external environment. However, traditional petroleum-based packaging films lack biodegradability and antimicrobial activity, which is not conducive to sustainable development and has been gradually replaced. In addition, excessive or improper use of antimicrobial agents leads to bacterial resistance. Although existing thermal sterilization technology can effectively prevent bacterial resistance, it will produce high energy consumption.
[0003] Chitosan has been a hot topic in the field of food packaging films due to its low cost, biodegradability and unique film-forming properties. It has good antibacterial properties after adding antimicrobial agents. Cationic ε-polylysine (ε-PL) is a natural food-grade antibacterial substance that is edible, biodegradable, high temperature resistant and non-toxic to the human body. However, it is easy to interact with the anionic components of the food matrix, resulting in turbidity, precipitation and hindering antibacterial activity. MXene Ti 3 C 2 As an emerging two-dimensional nanomaterial, MXene has been studied for loading or fixing antibacterial agents to improve antibacterial properties due to its high aspect ratio, large specific surface area and lack of drug resistance. In addition, MXene can convert light energy into heat energy under the irradiation of near-infrared light, making it an excellent photothermal agent. The photothermal antibacterial method is not only energy-saving, but also easy to control by near-infrared light irradiation, thus eliminating the disadvantage of high energy consumption of existing thermal sterilization.
[0004] Chinese patent application 202111460539.1 discloses "a method for producing a degradable frozen food packaging film with photothermal antibacterial function", which uses arabinoxylan extracted from wheat bran as the film substrate, adds plasticizers and antibacterial agents, and obtains a degradable frozen food packaging film with photothermal antibacterial function by casting, spraying photothermal agent and hydrophobic modification. However, the film has the disadvantages of complex operation process and long time consumption, and the film only explores the photothermal antibacterial effect on Listeria in frozen food. Chinese patent application 202110482889.1 discloses "a pectin-based nano-melanin edible photothermal antibacterial film and its preparation method and application", which adds natural melanin nanoparticles to the pectin base liquid, and obtains a safe and edible photothermal antibacterial film by casting and drying. However, its drying time is long, the illumination power is high, the sterilization time is long, and the film also only explores the sterilization effect on Listeria monocytogenes. Therefore, it is of great significance to develop a biodegradable photothermal antibacterial packaging film with easy operation, low light power and high sterilization efficiency. Summary of the invention
[0005] In order to overcome the problems of complicated and time-consuming preparation process of photothermal nanocomposite film, high illumination power, single sterilization type and long sterilization time in the prior art, the primary purpose of the present invention is to provide a method for preparing a degradable photothermal antibacterial composite film based on MXene-loaded ε-polylysine (ε-PL). First, the successfully etched MXene and ε-PL are prepared by electrostatic self-assembly to obtain MX@PL composite nanomaterials, and then added to chitosan (CS) film liquid containing glycerol plasticizer and stirred evenly, and after ultrasonic degassing, a photothermal antibacterial and degradable packaging film (CMP film) is prepared by solvent casting.
[0006] Another object of the present invention is to provide a degradable photothermal antibacterial composite film based on MXene loaded ε-polylysine prepared by the above preparation method.
[0007] Another object of the present invention is to provide the application of the above-mentioned MXene-loaded ε-polylysine degradable photothermal antibacterial composite film in food packaging.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing a degradable photothermal antibacterial composite film based on MXene-loaded ε-polylysine comprises the following steps:
[0010] (1) Mixing a MXene suspension and an ε-polylysine (ε-PL) solution, stirring for a period of time, collecting by centrifugation, and washing to obtain a MX@PL composite nanomaterial;
[0011] (2) preparing chitosan (CS) film liquid containing a plasticizer, mixing the chitosan film liquid and the MX@PL composite nanomaterial evenly, degassing, pouring the film, and drying to obtain a composite film.
[0012] Preferably, in step (1), the mass ratio of MXene to ε-polylysine (ε-PL) is 1:(0-4), wherein the mass of ε-polylysine is not 0; more preferably, the mass ratio of MXene to ε-polylysine (ε-PL) is 1:4.
[0013] Preferably, the concentration of the MXene suspension in step (1) is 1 to 10 mg / mL; more preferably 1 mg / mL.
[0014] Preferably, the concentration of the ε-polylysine (ε-PL) solution in step (1) is 0 to 4 mg / mL, wherein the concentration value is not 0; more preferably, it is 1 to 4 mg / mL.
[0015] Preferably, the solvents of the MXene suspension and the ε-polylysine (ε-PL) solution in step (1) are both water.
[0016] Preferably, the stirring time in step (1) is 1 to 5 hours; more preferably 1 hour.
[0017] Preferably, the washing of the precipitate collected by centrifugation in step (1) refers to washing with water.
[0018] Preferably, in step (2), the mass ratio of plasticizer to chitosan is 0.2-0.6:0.8-1; more preferably 0.3:1.
[0019] Preferably, in step (2), the plasticizer is glycerol.
[0020] Preferably, in the chitosan (CS) film solution containing a plasticizer in step (2), the concentration of chitosan is 10-20 mg / ml, more preferably 10 mg / ml; the solvent is an acetic acid aqueous solution with a volume fraction of 1-3%, more preferably an acetic acid aqueous solution with a volume fraction of 1%.
[0021] Preferably, the specific operation of preparing the chitosan (CS) film liquid containing the plasticizer in step (2) is: adding chitosan to an acetic acid aqueous solution, heating and stirring to dissolve, then adding the plasticizer, mixing evenly, to obtain the chitosan (CS) film liquid containing the plasticizer.
[0022] More preferably, the temperature of the heating and stirring dissolution is 40 to 60° C. and the time is 20 to 40 minutes.
[0023] Preferably, the MX@PL composite nanomaterial in step (2) accounts for 5-10% of the mass of chitosan; more preferably 5%.
[0024] Preferably, the degassing method in step (2) is ultrasonic degassing, and the ultrasonic time is 60 to 120 minutes.
[0025] Preferably, the drying time in step (2) is 40-60° C. and the time is 4-8 hours.
[0026] The above preparation method produces a degradable photothermal antibacterial composite film based on MXene loaded ε-polylysine.
[0027] The above-mentioned application of the degradable photothermal antibacterial composite film based on MXene loaded ε-polylysine in food packaging.
[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0029] (1) The present invention uses edible, high-temperature resistant cationic ε-PL and MXene two-dimensional nanomaterials with high specific surface area and negative charge to prepare MX@PL complexes through an efficient and green electrostatic adsorption self-assembly method. This not only solves the problem that cationic ε-PL easily interacts with the anionic components of the food matrix to hinder its antibacterial activity, but also obtains two-dimensional nanoparticles that can perform photothermal antibacterial activities.
[0030] (2) The photothermal antibacterial and biodegradable CMP composite membrane obtained by the present invention uses natural, cheap and biodegradable chitosan as the membrane substrate, and by adding the prepared MX@PL composite, the membrane has good ultraviolet shielding performance and mechanical properties.
[0031] (3) The photothermal antibacterial and degradable CMP composite film obtained by the present invention has very excellent oxygen barrier properties and can effectively prevent food oxidation caused by the packaging environment.
[0032] (4) The CMP composite film prepared by the present invention is subjected to 808 nm near-infrared laser with a laser power density of 1.5 W / cm 2 After irradiation for 3 minutes, it has a good bactericidal effect on common foodborne pathogens in food, among which Staphylococcus aureus and Escherichia coli have a photothermal antibacterial effect of more than 99%. At the same time, the film has good photothermal stability and repeatability. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The loading rate of ε-PL in the MX@PL composite at different mass ratios of ε-PL to MXene obtained in Example 1.
[0034] Figure 2 This is a schematic diagram of the principle of the photothermal antibacterial biodegradable packaging film prepared based on the MX@PL composite material obtained in Example 1.
[0035] Figure 3These are the light transmittance graphs of the CM film prepared in Comparative Example 2, the CS film prepared in Comparative Example 3, and the CMP-4 composite film prepared in Example 1.
[0036] Figure 4 The oxygen permeability graphs are of the CM membrane prepared in Comparative Example 2, the CS membrane prepared in Comparative Example 3, and the CMP-4 composite membrane prepared in Example 1.
[0037] Figure 5 The mechanical properties diagrams are of the CM membrane prepared in Comparative Example 2, the CS membrane prepared in Comparative Example 3, and the CMP-4 composite membrane prepared in Example 1.
[0038] Figure 6 The light and heat stability curves of the CM film prepared in Comparative Example 2, the CS film prepared in Comparative Example 3, and the CMP-4 composite film prepared in Example 1;
[0039] Figure A shows the temperature variation curves of the three films under 808nm laser irradiation, and Figures B and C show the temperature variation curves of the CM film and CMP-4 film under 1.5W / cm 2 Temperature change curve of photothermal cycle under 808nm laser irradiation, with 5 cycles.
[0040] Figure 7 The antibacterial effect diagram of the CM membrane prepared in Comparative Example 2, the CS membrane prepared in Comparative Example 3, and the CMP-4 composite membrane prepared in Example 1 on Staphylococcus aureus and Escherichia coli;
[0041] Figure A and Figure C are the antibacterial effect diagrams of the membranes prepared in the comparative example and the example on Escherichia coli and Staphylococcus aureus, respectively, and Figure B and Figure D are the antibacterial rates of the membranes prepared in the comparative example and the example on Escherichia coli and Staphylococcus aureus, respectively. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0043] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0044] Preparation method of MXene powder: Add 1.0g LiF to 20mL HCl (9mol / L) to obtain HF etching solution. After magnetic stirring, add 1g Ti 3 AlC 2The powder was slowly added to the etching solution and stirred at 35°C for 24h. The resulting slurry was centrifuged at 3500rpm for 5min and the etched product was washed with deionized water several times until a supernatant with a pH of 6-7 was obtained. The precipitate was then collected and ultrasonically treated with an appropriate amount of deionized water for 1h, and then centrifuged at 3500rpm for 1h to obtain MXene Ti 3 C 2 Finally, the MXene colloidal solution is freeze-dried to obtain MXene powder.
[0045] Comparative Example 1: Preparation method of MX@PL composite
[0046] First, 3 mg of MXene powder was added to 3 mL of deionized water and ultrasonically treated for 15 minutes using an ultrasonic cleaner to obtain a uniform and stable 1 mg / mL MXene suspension.
[0047] 2. According to the mass ratio of ε-PL:MXene of 0, 1, 2, 3, and 4, ε-PL with a mass of 0, 3, 6, 9, and 12 mg was dissolved in 3 mL of deionized water to form ε-PL solutions with concentrations of 0, 1, 2, 3, and 4 mg / mL, respectively.
[0048] 3. Add ε-PL solutions with concentrations of 0, 1, 2, 3, and 4 mg / mL to the MXene solution in the first step. After stirring at room temperature for 1 hour, the solution was centrifuged and the supernatant was retained and the mass concentration of ε-PL in the supernatant was immediately determined by methyl orange colorimetry and the loading rate was calculated. The precipitate collected by centrifugation was repeatedly washed with deionized water and freeze-dried to obtain the MX@PL composite material.
[0049] Comparative Example 2: Preparation method of CM composite membrane
[0050] 1. Dissolve 0.12 g CS in 12 mL of 1% acetic acid aqueous solution, stir at 50° C. for 30 min to obtain a CS solution, then add 0.036 g glycerol as a plasticizer, and stir magnetically for 1 h to obtain a plasticized CS film solution.
[0051] 2. Add 6 mg of MXene powder to the CS membrane solution and mix evenly to obtain a membrane-forming solution containing MXene nanomaterials, wherein the mass of MXene material is 5% relative to the mass of CS.
[0052] 3. Stir evenly and ultrasonicate for 60 minutes to remove bubbles in the membrane liquid, then slowly pour it into a culture dish with a diameter of 60 mm, and dry it at 50°C for 6 hours to obtain a CM composite membrane.
[0053] Example 1: Preparation method of CMP composite film
[0054] 1. Add 3 mg of MXene powder into 3 mL of deionized water and ultrasonicate for 15 minutes to obtain a uniform and stable MXene suspension with a concentration of 1 mg / mL.
[0055] 2. According to the mass ratio of ε-PL:MXene of 1, 2, 3, and 4, ε-PL with a mass of 3, 6, 9, and 12 mg was dissolved in 3 mL of deionized water to form ε-PL solutions with concentrations of 1, 2, 3, and 4 mg / mL, respectively.
[0056] 3. 3 mL of 1 mg / mL MXene suspension was mixed with 3 mL of 1, 2, 3, and 4 mg / mL ε-PL solutions and stirred at room temperature for 1 h. The solution was collected by centrifugation, the precipitate was washed with deionized water, and freeze-dried to obtain MX@PL-1, MX@PL-2, MX@PL-3, and MX@PL-4 composite nanomaterials.
[0057] 4. Dissolve 0.12 g CS in 12 mL of 1% acetic acid aqueous solution, stir at 50°C for 30 min to obtain a CS solution, then add 0.036 g glycerol as a plasticizer, and stir magnetically for 1 h to obtain a plasticized CS film solution.
[0058] 5. Add 6 mg of MX@PL-1, MX@PL-2, MX@PL-3, and MX@PL-4 composite nanomaterials to the CS membrane solution, respectively, and mix them evenly to obtain membrane-forming solutions containing MX@PL-1, MX@PL-2, MX@PL-3, and MX@PL-4 nanomaterials, respectively, where the mass of MX@PL material is 5% relative to the mass of CS.
[0059] 6. Stir evenly and ultrasonicate for 60 minutes to remove bubbles in the membrane liquid, then slowly pour it into a culture dish with a diameter of 60 mm, and dry it at 50° C. for 6 hours to obtain CMP-1, CMP-2, CMP-3, and CMP-4 composite membranes.
[0060] Comparative Example 3: Preparation method of CS film
[0061] 1. Dissolve 0.12 g CS in 12 mL of 1% acetic acid aqueous solution, stir at 50° C. for 30 min to obtain a CS solution, then add 0.036 g glycerol as a plasticizer, and stir magnetically for 1 h to obtain a plasticized CS film solution.
[0062] 2. The CS film was stirred evenly and ultrasonicated for 60 min to remove bubbles in the film. Then, it was slowly poured into a culture dish with a diameter of 60 mm and dried at 50 °C for 6 h to obtain a CS film.
[0063] The antibacterial films prepared in the above examples and comparative examples are tested and analyzed in various ways as follows:
[0064] (1) Comparative analysis of light transmittance
[0065] The CMP-4 film obtained in step 6 of Example 1 was cut into rectangular strips of 15 mm × 40 mm and placed on the sample holder of the UV spectrophotometer to measure the transmittance. Figure 3 As shown:
[0066] from Figure 3 It can be seen that compared with the CS film, the transmittance of the CMP-4 composite film in the near-ultraviolet region (200-400nm) and the visible light region (400-780nm) decreases to varying degrees, and has good ultraviolet shielding performance.
[0067] (2) Comparative analysis of oxygen permeability
[0068] The CMP-4 film obtained in step 6 of Example 1 was cut into a circular film with a diameter of 80 mm, and the gas permeability of the sample was measured using a gas permeability tester. Figure 4 As shown:
[0069] Figure 4 The oxygen permeability of CS, CM and CMP-4 films is Figure 4 It can be seen that after adding MX@PL nanocomposites, the CS membrane has a different -13 cm 3 cm / (cm 2 ·s·Pa)) compared to the CM membrane (2.8×10 -14 cm 3 cm / (cm 2 ·s·Pa)) and CMP-4 film (2.64×10 -14 cm 3 cm / (cm 2 ·s·Pa))'s oxygen permeability dropped significantly.
[0070] (3) Comparative analysis of mechanical properties
[0071] The CMP-4 film obtained in step 6 of Example 1 was cut into 10×90 mm rectangular strips, and the tensile properties of the film were tested by an electronic universal material testing machine. Figure 5 As shown:
[0072] Figure 5 is the tensile strength and elongation at break of CS, CM and CMP-4 films. Figure 5 It can be seen that due to the introduction of MX@PL nanomaterials, the tensile strength of CMP-4 is increased to 18.76MPa.
[0073] (4) Comparative analysis of photothermal stability
[0074] The CMP-4 film obtained in step 6 of Example 1 was cut into a circular film with a diameter of 10 mm and irradiated with an 808 nm near-infrared laser at a laser power density of 1.5 W / cm 2 The film sample was irradiated for 3 minutes, then the laser irradiator was turned off, and the laser was turned on again after it cooled naturally to room temperature. The above process was repeated five times, and the temperature change was recorded every 15 seconds.
[0075] Figure 6 The temperature variation curve of CMP-4 film in five cycles; Figure 6 It can be seen that during the five cycles of illumination, the fluctuations in the maximum temperatures of the CM film and the CMP-4 film were 1.59°C (the maximum temperatures were 74.08, 73.54, 74.6, 74.24 and 73.01, respectively) and 1.86°C (the maximum temperatures were 74.28, 73.72, 74.06, 72.42 and 74.24, respectively), and the fluctuations did not exceed 2.6%.
[0076] (5) Comparative analysis of photothermal antibacterial properties
[0077] The plate colony counting method was used to evaluate the CS film obtained in Comparative Example 3, the CM film obtained in Comparative Example 2, and the CMP-4 composite film obtained in Example 1 under the influence of an 808 nm near-infrared laser with a laser power density of 1.5 W / cm 2 Antibacterial activity under irradiation. The prepared films were cut into circular films with a diameter of 10 mm and placed in 24-well plates in turn. 1 mL of Escherichia coli (ATCC 25922) suspension or Staphylococcus aureus (ATCC 25923) suspension was dripped on the surface of different films. They were treated for 3 min with near-infrared laser (+NIR) or without near-infrared laser (-NIR). All samples were then placed in a 37°C biochemical incubator for 4 h. The bacterial solution with an appropriate dilution multiple was then spread on LB solid culture medium by the plate spreading method. The antibacterial rate was calculated after incubation at 37°C for 12 h. See Figure 2. Figure 7 As shown:
[0078] Figure 7 This is a diagram showing the antibacterial effects of the photothermal degradable antibacterial films prepared in the comparative example and the example on Staphylococcus aureus and Escherichia coli.
[0079] from Figure 7 It can be seen that without 808nm near-infrared light irradiation, the antibacterial rates of CM membrane and CMP-4 membrane increased to 65.16% and 90.13% respectively, compared with the antibacterial rate of CS membrane against Escherichia coli (51.34%). When 808nm infrared light irradiation was applied, the antibacterial rate of CS membrane against Escherichia coli did not change significantly, while the antibacterial rates of CM membrane and CMP-4 membrane increased significantly to 86.79% and 99.99%.
[0080] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a degradable photothermal antibacterial composite film based on MXene-loaded ε-polylysine, characterized in that: The following steps are involved: (1) Mixing the MXene suspension and the ε-polylysine solution, stirring for a period of time, collecting by centrifugation, and washing to obtain the MX@PL composite nanomaterial; (2) preparing chitosan film liquid containing plasticizer, mixing chitosan film liquid and MX@PL composite nanomaterials evenly, degassing, pouring films, and drying to obtain composite films.
2. The method for preparing a degradable photothermal antibacterial composite film based on MXene-loaded ε-polylysine according to claim 1, characterized in that: In step (1), the mass ratio of MXene to ε-polylysine is 1:(0-4), wherein the mass of ε-polylysine is not 0; In step (2), the MX@PL composite nanomaterial accounts for 5-10% of the mass of chitosan.
3. A method for preparing a degradable photothermal antibacterial composite film based on MXene-loaded ε-polylysine according to claim 1 or 2, characterized in that: In step (2), the mass ratio of plasticizer to chitosan is 0.2-0.6:0.8-1; The plasticizer is glycerol.
4. A method for preparing a degradable photothermal antibacterial composite film based on MXene-loaded ε-polylysine according to claim 1 or 2, characterized in that: The concentration of the MXene suspension in step (1) is 1 to 10 mg / mL; The concentration of the ε-polylysine solution in step (1) is 0 to 4 mg / mL, wherein the concentration value is not 0; The solvents of the MXene suspension and the ε-polylysine solution in step (1) are both water.
5. A method for preparing a degradable photothermal antibacterial composite film based on MXene-loaded ε-polylysine according to claim 1 or 2, characterized in that: In the chitosan film solution containing the plasticizer in step (2), the concentration of chitosan is 10-20 mg / ml; and the solvent is an acetic acid aqueous solution with a volume fraction of 1-3%.
6. A method for preparing a degradable photothermal antibacterial composite film based on MXene-loaded ε-polylysine according to claim 1 or 2, characterized in that: The stirring time in step (1) is 1 to 5 hours; The specific operation of preparing the chitosan film liquid containing the plasticizer in step (2) is: adding chitosan to an acetic acid aqueous solution, heating and stirring to dissolve, then adding the plasticizer, mixing evenly, to obtain the chitosan film liquid containing the plasticizer; The temperature of the heating and stirring dissolution is 40 to 60°C and the time is 20 to 40 minutes; The degassing method in step (2) is ultrasonic degassing, and the ultrasonic time is 60 to 120 minutes; The drying time in step (2) is 40-60° C. for 4-8 hours.
7. A method for preparing a degradable photothermal antibacterial composite film based on MXene-loaded ε-polylysine according to claim 1 or 2, characterized in that: In step (1), the mass ratio of MXene to ε-polylysine is 1:4; In step (2), the mass ratio of plasticizer to chitosan is 0.3:1; In step (2), the MX@PL composite nanomaterial accounts for 5% of the mass of chitosan.
8. The method for preparing a degradable photothermal antibacterial composite film based on MXene-loaded ε-polylysine according to claim 1, characterized in that: The concentration of the MXene suspension in step (1) is 1 mg / mL; The concentration of the ε-polylysine solution in step (1) is 1 to 4 mg / mL; In the chitosan film solution containing the plasticizer in step (2), the concentration of chitosan is 10 mg / ml; and the solvent is an acetic acid aqueous solution with a volume fraction of 1%.
9. A degradable photothermal antibacterial composite film based on MXene loaded ε-polylysine prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the degradable photothermal antibacterial composite film based on MXene loaded ε-polylysine as described in claim 9 in food packaging.
Citation Information
Patent Citations
Pectin-based nano melanin edible photo-thermal antibacterial film as well as preparation method and application thereof
CN113185732A
Production technology of degradable frozen food packaging film with photo-thermal antibacterial function
CN114058055A
Edible polysaccharide composite antibacterial membrane and preparation method thereof
CN109400968A
Chitosan / epsilon-polylysine intercalated montmorillonite antibacterial packaging film as well as preparation method and application thereof
CN114316378A
Two-dimensional metal carbide antimicrobial membrane and antimicrobial agent
WO2017083055A1
Cited By
Photo-start photo-thermal conversion temperature-sensitive slow-release antibacterial composite film as well as preparation and application thereof
CN122080462A